Gut Microbiota Modulation in Osteoporosis: Probiotics, Prebiotics, and Natural Compounds - Xufeng Chu; Hailin Xing; Minghao Chao; Panpan Xie; Lili Jiang (Metabolites)
Osteoporosis is a multifactorial bone metabolic disorder characterized by the deterioration of bone mass and microarchitecture, leading to increased fragility and fracture risk. Recent advances have revealed the critical role of the gut microbiota in the pathogenesis of osteoporosis, primarily mediated by metabolite-driven and immune-mediated interactions along the gut–bone axis. Dysbiosis, or microbial imbalance, can influence bone health by modulating host metabolism, immune function, and endocrine responses. While growing evidence suggests that gut microbiota modulation holds therapeutic potential for osteoporosis, the underlying mechanisms remain poorly understood. This review examines the latest findings on the role of prebiotics, probiotics, and natural bioactive substances in modulating the gut microbiota to improve bone health. We discuss how these interventions may restore microbial balance, enhance gut barrier function, and reduce systemic inflammation, thereby influencing bone metabolism. A deeper understanding of the gut–bone axis will pave the way for more targeted, effective, and personalized therapeutic strategies for osteoporosis prevention and treatment.